Searching and Displaying Al-Quran Verses from All Derivative Isim Makrifat Words to Support the Quranpedia Project - Dzaky Ikram; Eko Darwiyanto; Moch. Arif Bijaksana (STMIK Budi Darma, 2023)
Quranpedia is a website built to facilitate its users in searching for root words and verses containing the exact root words by following the structure of Wikipedia. This research employs the black box testing method to assess the functionality of the Quranpedia website. The results of the black box testing indicate that the website achieves a success rate of 94%, with an intuitive interface that aligns with the presentation of the Al-Quran. Additionally, this study involves root word testing to evaluate the accuracy of the search results for Quranic verses that share the exact root words. From these tests, an accuracy level of 85% is obtained. The findings of this research demonstrate that Quranpedia successfully fulfills its primary goal by providing a reliable and comprehensive reference source for the Muslim community. With an engaging interface and an ongoing commitment to improving accuracy, Quranpedia is expected to assist the Muslim community in deepening their understanding and appreciation of the sacred book, the Al-Quran.